Proposed Model for The Factors Influencing Muslim Investors in Choosing Islamic Unit Trust Funds - Yusuff, Noraini; Mansor, Fadillah (Gbseglobal, 2016)
The purpose of this study is to identify the factors which are influencing Muslims investor in choosing Islamic unit trust funds as one of their saving alternatives. The connections among the factors have not been fully established in decision making area. We developed a model and testable propositions of the relationships between religiosity, Islamic financial literacy and product knowledge with the dependent variable, decision making in Islamic unit trust funds. The target respondents for this study will be the Muslim investors in Islamic unit trust funds in Malaysia